Terrorist Assemblages : Homonationalism in Queer Times - Puar, Jasbir K., 1967- (Book collections on Project MUSE., 2007)
Puar argues that configurations of sexuality, race, gender, nation, class and ethnicity are realigning in relation to contemporary forces of securitization, counterterrorism, and nationalism, and examines how liberal politics serve to incorporate certain queer subjects into the fold of the nation-state.